The political economy of EEC relations with African, Caribbean and Pacific States : contributions to the understanding of the Lomé Convention on North-South relations - Long, Frank (Pergamon P. OxfordGB, 1980)
Seeks to contribute to the understanding of the political economy of EEC/ACP relations, to deal with some of the central issues affecting such relations and attendant conventions. Focuses on the issues that include aspects of renegotiation, trade, indexation, STABEX, technology transfer and market access.